Supply Chain Management Development for Organization of Public Services in the City: The Experience of Moscow - Natalia V. Medvedeva; Elena E. Kabanova; Ekaterina A. Vetrova; Maxim S. Kozyrev; Stanislav I. Dorzhinkevich (International Journal of Supply Chain Management, 2019)
Abstract- The present article discusses the practical aspects of organizing provision of public services in Moscow by using supply chain strategy. The main difficulties of providing public services in multifunctional centers (MFC) of the capital region are studied, and the main limitations of provision of public services in modern Russian conditions are revealed. Currently, one of the most important tasks of the state is to provide modern, timely and high-quality public services to citizens. In the process of providing public services, the state pays great attention to the development of feedbacks from citizens and uses new ways of providing public services. In Moscow, a â€œSingle portal of state and municipal services (functions)â€ has been created, which provides electronic access to services. With its help, the applicant can submit an application and other necessary documents, and also learn about the progress of the public service. The result of organization of MFC is that the process of providing public services has become more accessible, convenient and much more comfortable. In recent years, the form of activity of MFC has undergone significant changes, mainly due to the rapidly growing needs of citizens. Most changes occurred in the Moscow Multifunctional Center because of the fast growth in demand for services and desire to improve the quality of services. However, problems of citizens' awareness of the newly created services and the possibilities of obtaining them have still remained unresolved.